KAJIAN METODE DAN PENGKLASIFIKASIAN ALMAKKY DAN ALMADANY - Hamdiah Hamdiah; Hanna Hanna (CV. Adiba Aisha Amira, 2022)
The concept of verses and letters that fall into the categories of makkiyah and madaniyah. Where are various orders or prohibitions in the Shari'a based on makkiyah and madaniyah arguments. Al-Qur'an is the word of Allah SWT which was revealed to Rasulullah SAW through the intermediary of the angel Gabriel. The period of his descent is divided into two periods, namely before and after the hijrah of Rasulullah SAW. In general, the verses revealed in Mecca and its surroundings before the hijrah are called Makkiyah, and the verses revealed in Medina and its surroundings after the hijrah are called Madaniyah